Topsis Method To Determine Recipients Of Covid 19 Social Assistance Funds - Artika Surniandari; Hilda Rachmi; Lisda Widiastuti (Institute of Computer Science (IOCS), 2021)
Pandemic and social restrictions are inseparable things, with the existence of these restrictions, several sectors of life have changed, including the economic sector, the number of unemployed due to layoffs has increased because a number of companies have difficulty covering operational costs. The central government finally took a policy to provide social assistance to residents who met the criteria of being poor and the determination was left to the local government. The method used to assist decision making to determine suitable beneficiaries is to use TOPSIS. With the TOPSIS method, it is hoped that the assessment will be more precise because it is based on predetermined criteria and weight values ??so that more accurate results will be obtained. In this research, the results obtained from ranking to determine the priority for citizens to get Covid 19 social assistance and the results of residents who do not earn because they do not work while having dependents of more than 5 people who are more than 30 years old get the top priority